2021
DOI: 10.1080/02673843.2021.1959355
|View full text |Cite
|
Sign up to set email alerts
|

Can emotional intelligence training cause a cease in tobacco smoking among school-going adolescents?

Abstract: Emotional intelligence training intervention was used to reduce tobacco smoking consumption among school-going adolescents in state of Edo, Nigeria. The pre-test post-test experimental design was observed. While the 90 participants were purposively selected from the schools that were randomly assigned to EIT (45) and control groups (45). Analysis of covariance and independent t-tests were used for data analysis. The emotional intelligence training intervention significantly improved tobacco smoking cessation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Consequently, emotional intelligence training can effectively facilitate individuals' adequate adaptation to health conditions [32], while individuals with higher levels of emotional intelligence can better benefit from prevention programs. In a previous study, an educational intervention based on emotional intelligence was used to reduce smoking, the results of which showed that it was effective in smoking cessation [33,34]. Overall, it has been reported by various scholars that educational programs based on emotional intelligence can be beneficial for reducing smoking dependence and overall adopting behaviors that reduce smoking intention.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Consequently, emotional intelligence training can effectively facilitate individuals' adequate adaptation to health conditions [32], while individuals with higher levels of emotional intelligence can better benefit from prevention programs. In a previous study, an educational intervention based on emotional intelligence was used to reduce smoking, the results of which showed that it was effective in smoking cessation [33,34]. Overall, it has been reported by various scholars that educational programs based on emotional intelligence can be beneficial for reducing smoking dependence and overall adopting behaviors that reduce smoking intention.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Consequently, emotional intelligence training can effectively facilitate individuals' adequate adaptation to health conditions (Karimzadeh et al, 2012), while individuals with higher levels of emotional intelligence can better benefit from prevention programs (Trinidad et al, 2004). In previous research, an educational intervention based on emotional intelligence was used to reduce smoking, the results of which showed that it was effective in smoking cessation (Lawrence & Egbule, 2021). Overall, it has been reported by various scholars (Yadegar Tirandaz et al, 2020;Bhochhibhoya & Branscum, 2015;Trinidad et al, 2004;Psychology Trinidad & Johnson, 2002) that educational programs based on emotional intelligence can be beneficial in reducing of smoking addiction and overall the adoption of behaviors that reduce the intention to smoke.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%